The use of authentic material by teachers to enhance the reading skill of students of Advanced Intensive English I from the Foreign Languages Department, University of El Salvador, semester II, year 2014 - Amaya Rodas, Claudia Verónica; Chavarria Garcia, Karol Elizabeth; Hernández Alfaro, Jorge Alberto; Garay Salinas, Ricardo; Ayala, Edgar Nicolás (San Salvador : Universidad de El Salvador, 2015)
This document contains valuable information about the undergraduate research work “The use of authentic materials by teachers to enhance the Reading skill of students of Advanced Intensive English I.” This investigation was carried out from April 2014 to December 2014. It provides detailed information on the use of authentic materials by teachers in the improvement of the reading skill to the advanced level ́ students of Licenciatura en Idioma Inglés opción Enseñanza at the Foreign Language Department in the Main Campus of the University of El Salvador during the semester II, year 2014.
Anexos.
Tesis para optar al titulo de -- (Licenciatura en Idioma Inglés opción enseñanaza) -- Universidad de El Salvador, San Salvador, 2015
Bibliografía: hoja 51-52
Audiencia general
Keywords: Inglés -- Enseñanza; Lenguaje y lenguas -- Enseñanza